Strengthening Firm Value through ESG Assurance, Internal Audit, and Enterprise Risk Management: Asessing Audit Quality as Potential Boundary Condition - Icih; Sulis Setiawati; Norhanizah Johari; Sri Mulyati (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examined the influence of ESG assurance, internal audit and enterprise risk management on firm value and analyzed the role of audit quality as a moderating variable. The study was conducted on basic materials companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period, using agency theory and signaling theory. Design/methodology/approach – The research employed a quantitative method. The sample was selected using purposive sampling within the basic materials sector. Firm value was measured using Tobin's Q, ESG assurance was measured using the existence of external assurance, internal audit implementation was proxied by its implementation indicators, ERM was measured using a strategy-based and operations-based index, and audit quality was measured using the reputation of the Public Accounting Firm. Data were analyzed using moderated regression analysis (MRA). Finding/Results – The F-test results demonstrate that the regression model is overall statistically significant in explaining firm value. Individually, however, only internal audit implementation exerts a significant positive effect on firm value, whereas ESG assurance and ERM do not exhibit partial significance. This indicates that the simultaneous significance of the model is primarily driven by the robust individual contribution of internal audit practices. Originality/Value – This study contributes to the governance and sustainability literature by providing evidence from the basic materials sector, a high-risk and capital-intensive industry. The findings highlight the importance of internal audit implementation as a governance mechanism that is directly valued by investors, while ESG assurance and ERM appear to have limited individual relevance in market valuation. The results also suggest that governance mechanisms may be more effective when implemented collectively rather than separately. Practical implications emphasize the need for stronger integration between internal audit, risk management, and sustainability practices, while regulators may consider enhancing ESG reporting standards to improve transparency and comparability.